Academic entrepreneurs? - Birley, Sue; McMullen, Ed; Myers, Andrew (Cranfield University, 1989)
Entrepreneurial education has exploded over the past ten years in both the United States and the United Kingdom. In the USA there are now more than 50 institutions seeking academics to fill endowed posts; in the UK, there are more than 200 courses in small business in institutions of Higher and Further Education. The reasons for the growth has been essentially the same in both countries - in time of economic decline, with large firms shedding labour, new firms and small firms have been seen as a significant strand in future strategies. As a result, academic institutions have been forced to respond to a demand from both students and potential entrepreneurs, a demand fanned by a growing band of “academic entrepreneurs” . . . ..but are they?